Cluster Approach to the Development of Rural Tourism - Evgenia V. Kulagina, Olga V. Lukina , Maria A. Gritsay , Venera T. Balgabayeva , Marina B. Dyuzheva (International Journal of Advanced Science and Technology, 2020)
The relevance of the conducted study is due to the recent call for the use of the cluster approach as a form of organization for the further development of rural regional tourism in Russia and Kazakhstan. In this regard, this article is aimed at disclosing theoretical and practical issues of the application of the cluster approach to the development of rural tourism. The methodological base of the research was represented by the methods and tools for analyzing expert assessments, mathematical statistics, modeling, tabular and graphical interpretation of empirical information. The article presents the theoretical aspects of the cluster approach to the development of tourism and suggests clustering potential of rural tourist areas; the article also reviews an empirical study of the subject. As an example, the presented paper examines the use of the cluster approach for the development of rural tourism in the Omsk region (Russian Federation), which is an industrial region with developed agriculture; the named region also has the necessary tourist and recreational resources. The materials of the article are of practical value for managing the establishment of clusters of rural tourism and can be applied to various regions of Russia, Kazakhstan, and other countries. The recommendations developed in the study can be of practical use for hospitality specialists, as well as for teachers, students, and scientists involved in the development of rural tourism.